پاکستان میں عورت کی سماجی و قانونی حیثیت : مسائل اور حل: Socio-Legal Status of Women in Pakistan: Problems and Remedies (Al-Qamar, 2023)
A woman is an important part of society and the role of a woman as a sister, daughter, wife, and mother has always been very important in the society. In this research paper, the status of women has been described in the light of prevailing Pakistani laws. It argues that Pakistani society customs has profound effects on all aspects including social, religious, political, economic, educational, medical and hereditary matters. Nowadays, Pakistani women are facing many social, political, religious, educational, medical and economic problems. Through laws, various social, political, educational, medical, religious problems of Pakistani women have been solved, so the prevailing laws of Pakistan provide guidance to women in different ways in every sphere of life. They provide them with all kinds of legal rights and along with various protections in the society, but these laws are not being implemented properly. It concludes that in order to ensure the rights of women and their better social status in the society these laws must be implemented.
Keywords: Women; Pakistan; Socio-Legal Status; Problems; Solutions